Colonialism and the object.: empire, material culture, and the museum - Barringer, Tim.; Flynn, Tom. (London : New York : Routledge, 1998)
Drawing together an international group of scholars from a variety of disciplinary and cultural backgrounds, Colonialism and the Object explores the impact of colonial contact with other cultures on the material culture of both the colonized and the imperial nation. The book includes intensive case-studies of objects from India, Pakistan, New Zealand, China and Africa, all of which were collected by, or exhibited in, the institutions of the British Empire, and key chapters address issues of radical identity across cultural barriers, and the hybird styles of objects which can emerge when cultures meet. Colonialism and the Object is essential reading for all those interested in post-colonial theory, museum studies, material culture and design history
Includes bibliographical references (p. 205-216) and index.
Keywords: Art, Colonial. -- Foreign influences; Art